2004
DOI: 10.1074/jbc.m400255200
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 Reduces α-Synuclein Aggregation and Toxicity

Abstract: Aggregation and cytotoxicity of misfolded ␣-synuclein is postulated to be crucial in the disease process of neurodegenerative disorders such as Parkinson's disease and DLB (dementia with Lewy bodies). In this study, we detected misfolded and aggregated ␣-synuclein in a Triton X-100 insoluble fraction as well as a high molecular weight product by gel electrophoresis of temporal neocortex from DLB patients but not from controls. We also found similar Triton X-100 insoluble forms of ␣-synuclein in an ␣-synuclein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
407
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(429 citation statements)
references
References 70 publications
20
407
0
2
Order By: Relevance
“…In a cell culture model, the overexpression of Hsp70 reduced high molecular weight and detergent insoluble α-synuclein, as well as reducing total α-synuclein levels. This corresponded with a reduction in α-synuclein-induced toxicity [16]. Consistent with these findings, the expression of Hsp70 in an α-synuclein transgenic mouse model was also able to reduce high molecular weight and detergent insoluble species [16].…”
Section: Pdsupporting
confidence: 72%
See 2 more Smart Citations
“…In a cell culture model, the overexpression of Hsp70 reduced high molecular weight and detergent insoluble α-synuclein, as well as reducing total α-synuclein levels. This corresponded with a reduction in α-synuclein-induced toxicity [16]. Consistent with these findings, the expression of Hsp70 in an α-synuclein transgenic mouse model was also able to reduce high molecular weight and detergent insoluble species [16].…”
Section: Pdsupporting
confidence: 72%
“…This corresponded with a reduction in α-synuclein-induced toxicity [16]. Consistent with these findings, the expression of Hsp70 in an α-synuclein transgenic mouse model was also able to reduce high molecular weight and detergent insoluble species [16]. Further in vivo studies in both Drosophila melanogaster and mice showed that the Hsp70-mediated reduction in α-synuclein aggregation corresponded with an increase in dopaminergic neuron survival, enabling the preservation of striatal dopamine levels [17,18].…”
Section: Pdsupporting
confidence: 67%
See 1 more Smart Citation
“…Hsp70 members are highly multifunctional proteins that have been shown to play a key role in proteome maintenance, such as in de novo protein folding (co-or post-translational), protein translocation across membranes (Lyman and Schekman, 1997;Matlack et al, 1999;Young et al, 2003), refolding of stress damaged proteins (Ben-Zvi et al, 2004;Schroder et al, 1993;Sharma et al, 2010), in preventing protein aggregation (Auluck et al, 2002;Broadley and Hartl, 2009;Klucken et al, 2004;Sakahira et al, 2002;Warrick et al, 1999), disaggregation (Ben-Zvi and Goloubinoff, 2001;Diamant et al, 2000;Liberek et al, 2008;Shorter, 2011) and degradation of irreparable misfolded proteins (Bercovich et al, 1997;Fisher et al, 1997;Urushitani et al, 2004). These essential and diverse cellular functions of Hsp70 are attributed to its physical interaction with various co-chaperones such as Hsp40, NEFs and with proteins such as HIP, HOP and CHIP.…”
Section: Ii41121 the Hsp70 Chaperone Systemmentioning
confidence: 99%
“…1 Among them, three potential candidates have been recently identified, namely b-synuclein, Parkin and heat-shock proteins (Hsp). 1,17 b-Synuclein belongs to a larger family of synaptic proteins that includes a-synuclein and g-synuclein. 18 b-Synuclein is an abundant synaptic protein originally identified as PNP14 in the bovine brain.…”
Section: Introductionmentioning
confidence: 99%